Validating the Physical Educators’ Attitude Toward Teaching Individuals with Disabilities III (PEATID III) Instrument for Physical Education Teachers: Supporting Inclusive Education in Indonesia - Sari, Merlina; Nazirun, Novia; Purwanto, Sugeng; Rahmadani, Ahmad; Omar-Fauzee, Mohd Sofian; Abdullah, Nagoor Meera (Physical Education Theory and Methodology, 2025)
Objectives. This study aimed to validate the Physical Educators’ Attitude Toward Teaching Individuals with Disabilities III (PEATID III) instrument in the context of physical education in Indonesia, especially in Pekanbaru City. Materials and methods. This study involved 120 physical education teachers in Pekanbaru City who were selected by purposive sampling. Inclusion criteria for respondents included teachers who had experience teaching students with disabilities in regular classes and were willing to participate in this study. To examine Physical Educators’ Attitudes Toward Teaching Individuals with Disabilities III (PEATID III) in the context of physical education, this instrument consists of 12 statements that measure three aspects of teacher attitudes, namely: (i) outcomes of teaching students with disabilities, (ii) impact on student learning, and (iii) need for additional training. Results. All items’ Content Validity Ratio (CVR) values were over 0.60, indicating high relevance to Indonesian social and cultural environment. Сonstruct validity was tested using confirmatory factor analysis (CFA) and found a satisfactory model fit (χ²/df = 2.31; CFI = 0.93; RMSEA = 0.06). The instrument’s Cronbach’s alpha coefficient was 0.88, indicating strong internal consistency. Descriptive analysis showed that physical education teachers’ attitudes towards teaching students with disabilities tended to be positive (M = 3.87; SD = 0.64). Teachers with more than five years of experience and additional training had more inclusive attitudes. Conclusions. This study makes a significant contribution in providing a reliable instrument to evaluate teachers’ attitudes towards inclusive education, supporting the development of policies and training programs relevant to local needs. The findings also provide a basis for further research that focuses on strengthening inclusive education in Indonesia through a more comprehensive and representative approach.